Effect of type and concentration of cryoprotectant on post-thaw survivability of vitrified porcine follicular oocytes - KALITA, KRISHNA; DEKA, B C; BISWAS, R K; BARUA, P M; BORAH, P; DUTTA, D J; DAS, S K (The Indian Journal of Animal Sciences, 2018)
A total of 950 and 510 oocytes with two or more cumulus cell layers adhered to zona pellucida obtained by aspiration from follicles (2–8 mm dia) of 315 and 135 abattoir porcine ovaries, respectively, were utilized in the study to find the effect of cryoprotectant and concentration on post-thaw survivability of porcine follicular oocytes. Vitrified post-thaw oocytes with intact zona pellucida and vitelline membrane, normal spherical shape and dark and evenly granulated cytoplasm under a stereo-zoom microscope were considered as viable. Out of the 10 cryoprotectant treatments i.e. ethylene glycol (EG), propylene glycol (PG), dimethyl sulphoxide (DMSO), glycerol (GL), EG + PG, EG + DMSO, EG + GL, PG + DMSO, PG + GL and DMSO + GL used for vitrification of oocytes at a concentration of 35%, the post-thaw survivability rate was the highest in EG +DMSO followed by EG + PG group which had significantly higher mean post-thaw survived oocytes as compared to GL, PG + DMSO, PG + GL and DMSO + GL groups. Exposing the oocytes to 30, 35 and 40% of EG + DMSO and EG + PG yielded no significant difference in post-thaw survivability rate of vitrified oocytes, although the highest value was obtained with 35%. It was concluded that 35 to 40% EG + DMSO yielded efficient vitrification of porcine oocytes.